Neonatal exposure of rats to recombinant follicle stimulating hormone increases adult Sertoli and spermatogenic cell numbers - Sarah J. Meachem; Robert I. McLachlan; David M. de Kretser; David Robertson; Nigel G. Wreford (1996)
It is believed that Sertoli cells support a finite number of germ cells and that Sertoli cell number may help determine the spermatogenic capacity of the adult. In the rat, Sertoli cells divide during fetal and early postnatal life, a process controlled in part by FSH. This study examined the effect of recombinant human FSH on postnatal testicular development and the impact of neonatal FSH exposure on the adult animal. Sprague-Dawley rats received FSH (200 IU/kg s.c.) daily from birth (Day 1) until Day 5, 10, 15, and 20. In a second experiment, animals received FSH for the first 10 or 15 days of life and were killed at Day 90. Sertoli and spermatogenic cell numbers were determined by stereological methods (the optical disector technique). FSH treatment significantly (p < 0.001) increased testicular weights (135%, 193%, and 173% of controls at Days 10, 15, and 20, respectively). The absolute volume of the epithelium and interstitium increased significantly as a result of increases in tubule diameter and length. In response to FSH treatment, the number of Sertoli cells increased significantly (p < 0.01) to 168%, 139%, and 151% of control numbers at Days 10, 15, and 20, respectively. After 15 days of FSH treatment, the numbers of spermatogonia and spermatocytes also increased (169% and 220% of control, p < 0.01, p < 0.001, respectively). The labeling index of Sertoli cell nuclei, as determined by bromodeoxyuridine incorporation, was unaffected by FSH treatment, with cessation of Sertoli cell division occurring as normal at Day 15. FSH treatment for the first 10 or 15 days of neonatal life resulted in testicular hypertrophy in adulthood (testis weight 118% and 124% of control, respectively). Similar increases were seen in the absolute volume of seminiferous epithelium and lumen, which were attributed to an increase in tubule length. Sertoli cell numbers increased to 113% and 149% of control after 10 and 15 days, respectively, of FSH exposure, with similar increases in round and elongated spermatid numbers. We conclude that exposure of the neonatal rat to recombinant FSH results in testicular hypertrophy with increases in seminiferous tubule volume and length and proportionate increases in Sertoli and germ cell numbers. This trophic effect of increased perinatal FSH exposure persists into adulthood to augment the spermatogenic potential of the rat.